Genetic Counseling For The Mentally Ill in University Malaya Medical Center: Are We There Yet? - Amer Siddiq, A.N.; Juliana Lee, M.H. (2008)
Introduction: This is a report of a Malay woman with bipolar illness who has many other family members with mental illness. She is of childbearing age as is her sister who also has a similar condition. They both are uncertain whether to have children in view of their condition. We are well aware now that certain mental illnesses including mood disorders have genetic predisposition. However we are not sure on how to use this information in a local setting. This question infrequently arises but answers are not as easily sought. In University Malaya Medical Center (UMMC), we have a Genetic Service which maybe of some assistance in handling such cases as above. This presentation will attempt to highlight the possibility of using genetic counseling services in the management of high-risk individuals with mental illness. patients. Objective: To identify the potentiality of using genetic services in the management of treating mentally ill patient. Method: A case report study. Conclusion: This case report attempts to show the usefulness and importance of genetic counseling services in the management of high-risk individuals with mental illness. It is hoped that this report demonstrates the need to incorporate genetic counseling services in the multidisciplinary management of mentally ill patients.